Does Walking with a Load Affect Asymmetry in Bilateral Lower Extremity Mechanics? - Seunghyun Hyun (Korea Institute of Sport Science, 2024)
PURPOSE This study sought to analyze the velocity and asymmetry between bilateral lower extremity mechanics according to the load during walking. METHODS A total of 14 adults with right leg dominance participated in this study (Male=7, Female=7). We respectively applied 30% of body weight load carriage on the subjects. Gait characteristics were analyzed with 3-dimensional cinematography and ground reaction force (GRF) system consisted of a center of gravity (COG) velocity, center of pressure (COP) area, leg stiffness, and GRF components. RESULTS Change in velocity of the maximum-minimum COG showed statistically significant in the main effect of load. The 1st anterior-posterior GRF (braking force) and vertical GRF were statistically significant in the main effects of load and bilateral lower limbs. The 2nd anterior-posterior GRF (propulsive force) was statistically significant in the main effect of load. COP area and leg stiffness exhibited statistically significant differences in the main effects of load and bilateral lower limbs. Interaction was observed in the vertical GRF, COP area. Furthermore , one-way variance analysis revealed load main effect had a greater influence on the increase in the magnitude of the vertical GRF and COP area than the asymmetry of bilateral lower limbs. CONCLUSIONS This study revealed the differences in asymmetry between the dominant and non-dominant lower limbs according to the load during walking. These findings may explain the differences shock attenuation and stress mechanisms between the bilateral lower limbs.